Dysfunction of ATP7B Splicing Variant Caused by Enhanced Interaction With COMMD1 in Wilson DiseaseSummary - Donghu Zhou; Huaduan Zi; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Bei Zhang; Wei Zhang; Xiaojuan Ou; Jidong Jia; Jian Huang; Hong You (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: The association between Wilson disease and various ATP7B mutations is well-established; however, the molecular mechanism underlying the functional consequence of these mutations, particularly the splicing mutations, remains unclear. This study focused on the ATP7B c.1543+1G>C variant, to reveal a universal pathogenic mechanism of the ATP7B mutants with altered N-terminus. Methods: The splicing assay and RNA pull-down were performed to explore the mechanism of the aberrant splicing. The ATP7B knockout HuH-7 cell line and Atp7b-/- mice were created, and the functional consequence of the mutant ATP7B were evaluated in vitro and in vivo. Results: The c.1543+1G>C mutation resulted in the skipping of ATP7B exon 3, and the mutant ATP7B showed a loss of trans-Golgi network localization and was degraded via the ubiquitin-proteasome pathway, facilitated by enhanced interactions with COMMD1. Elevated intercellular copper concentration and reduced survival rate were observed in HuH-7 cells expressing mutant ATP7B. Restoration of wild-type ATP7B in Atp7b-/- mice resulted in a substantial improvement in phenotype, whereas mice treated with mutant ATP7B did not demonstrate equivalent benefits. Conclusions: Our research investigated the pathogenicity and mechanism of ATP7B c.1543+1G>C variant, with particular focus on its enhanced interaction with COMMD1 as a potential universal mechanism contributing to the dysfunction of various ATP7B variants. These findings provide a foundation for the development of innovative therapeutic strategies that target abnormal splicing events in a range of hereditary diseases, including Wilson disease.